Neurological sequelae of long COVID: a comprehensive review of diagnostic imaging, underlying mechanisms, and potential therapeutics - Talkington, Grant McGee; Kolluru, Paresh; Gressett, Timothy E.; Ismael, Saifudeen; Meenakshi, Umar; Acquarone, Mariana; Solch-Ottaiano, Rebecca J.; White, Amanda; Ouvrier, Blake; Paré, Kristina; Parker, Nicholas; Watters, Amanda; et al. (Frontiers in Neurology, 2025)
One lingering effect of the COVID-19 pandemic created by SARS-CoV-2 is the emergence of Long COVID (LC), characterized by enduring neurological sequelae affecting a significant portion of survivors. This review provides a thorough analysis of these neurological disruptions with respect to cognitive dysfunction, which broadly manifest as chronic insomnia, fatigue, mood dysregulation, and cognitive impairments with respect to cognitive dysfunction. Furthermore, we characterize how diagnostic tools such as PET, MRI, EEG, and ultrasonography provide critical insight into subtle neurological anomalies that may mechanistically explain the Long COVID disease phenotype. In this review, we explore the mechanistic hypotheses of these neurological changes, which describe CNS invasion, neuroinflammation, blood-brain barrier disruption, and gut-brain axis dysregulation, along with the novel vascular disruption hypothesis that highlights endothelial dysfunction and hypoperfusion as a core underlying mechanism. We lastly evaluate the clinical treatment landscape, scrutinizing the efficacy of various therapeutic strategies ranging from antivirals to anti-inflammatory agents in mitigating the multifaceted symptoms of LC.